The effect of extrusion of the filling material on the periapical status - M. Yu. Pokrovsky; T. P. Goryacheva; A. М. Pokrovskiy; O. А. Aleshina (Эндодонтия Today)
AIM. To identify the relationship between the extrusion of filling material and the periapical status when using CBCT.MATERIALS AND METHODS. 500 CBCT scans of patients were studied, the condition of 2915 teeth and 6142 root canals were assessed. The cases of endodontic treatment, which are associated with the overfilling (extrusion) of the filling material, are analyzed. Canals with an apical level of the root seal – 0–2 mm from the X-ray apex of the root (3533 root canals) were considered as a control group. In all cases, the periapical status was assessed. Methods of medical statistics have been applied.RESULTS. Extrusion of the filling material was determined in 10.7% of the total number of endodontically treated root canals. The material was located: 81.7% in bone tissue, 13% in the maxillary sinus, 4.7% under oral mucosa of the alveolar process, 0.6% in the mandibular canal and/or mental foramen. In the control group, the periapical status “unchanged” was noted in 89.5% of cases, pathological changes were detected in 10.5% of cases. The remaining percentage of the total number of root canals was made up of underfilled or missed root canals without taking into account the periapical status. A lower incidence of periapical changes was determined when filling material was extruded into bone tissue (7.4%), than at the optimal level of root canal filling (11.7%). The differences between the groups were found to be statistically significant. Practical recommendations have been formulated to improve the accuracy of diagnosis, proper planning and increase the effectiveness of endodontic treatment.CONCLUSIONS. Extrusion of filling material into bone tissue is more often associated with effective endodontic treatment than optimal filling of the root canal along the apical border of the root filling. In this regard, the extrusion of the filling material into the bone tissue, in the case of a formed apical stop, can be considered a sign of successful obturation of the root canal.